Fast Software Encryption 21st International Workshop, FSE 2014, London, UK, March 3-5, 2014. Revised Selected Papers - Cid, Carlos; Rechberger, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 21st International Workshop on Fast Software Encryption, held in London, UK, March 3-5, 2014. The 31 revised full papers presented were carefully reviewed and selected from 99 initial submissions. The papers are organized in topical sections on designs; cryptanalysis; authenticated encryption; foundations and theory; stream ciphers; hash functions; advanced constructions.
Designs -- Cryptanalysis -- Authenticated encryption -- Foundations and theory -- Stream ciphers -- Hash functions -- Advanced constructions.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Coding theory; Management information systems; Computer Science; Data Encryption; Systems and Data Security; Management of Computing and Information Systems; Coding and Information Theory; Electronic books